Association Between Renal Dysfunction and Low HDL Cholesterol Among the Elderly in China - You, Aijun; Li, Yaxin; Tomlinson, Brian; Yue, Longfei; Zhao, Kaijie; Fan, Huimin; Liu, Zhongmin; Zhang, Yuzhen; Zheng, Liang (Frontiers in Cardiovascular Medicine, 2021)
Objective: Chronic kidney disease (CKD) and cardiovascular disease (CVD) have a high morbidity and mortality among the elderly. Low levels of high-density lipoprotein cholesterol (HDL-C), a traditional risk marker for CVD, are common in CKD patients. Little is known about the association of low HDL-C with renal dysfunction in the community dwelling population. Methods: This was a population-based cross-sectional study included 4753 participants enrolled in a prospective study, the Shanghai Elderly Cardiovascular Health (SHECH) Study. Estimated glomerular filtration rate (eGFR), calculated by the Chinese Modified Diet in Renal Disease (C-MDRD), was used to assess renal dysfunction. Associations between renal dysfunction and low HDL-C were evaluated using multiple logistic regression models and restricted cubic splines. Results: Of 4649 individuals who met inclusion criteria, 620 (13.34%) had low HDL-C at < 40 mg/dL. In the fully adjusted model, lower eGFR of <60 mL/min/1.73m2 (OR, 2.03; 95% CI, 1.21-3.43) and marginal eGFR of 60 to 90 mL/min/1.73m2 (OR, 1.26; 95% CI, 1.01-1.58) were significantly associated with low HDL-C, compared with normal eGFR of ≥90 mL/min/1.73m2. Moreover, consistent findings were obtained in secondary analyses using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. Fully adjusted cubic spline models indicated a significant dose-response relationship between eGFR and low HDL-C (P for nonlinearity, 0.52). Conclusion: In this general elderly population, renal dysfunction was independently and significantly associated with low HDL-C, and the prevalence of low HDL-C increased with decreasing eGFR, such that even slight changes in renal function may be associated with altered lipid levels.